SYNERGY OF RELIGION AND CULTURE: HARMONIZATION OF RELIGION AND CUSTOMS OF THE PEGAYAMAN VILLAGE MUSLIM COMMUNITY, SUKASADA SUB-DISTRICT, BULELENG, BALI - FAIZAH, ROHMATUL; YUSRINA, JIHAN AVIE (Tarbawi : Jurnal Pendidikan Islam, 2024)
Religion is a sensitive issue that is quickly brought up amidst the diversity of Indonesian society. Moreover, minority groups are perceived to have less freedom of movement among the traditions and customs of the majority. The dynamics between religion and customs must be addressed wisely and judiciously by all elements of society to form a harmonious and peaceful life in a pluralistic society. In this case, sensitivity between religious communities to tolerate each other's customs and traditions without sacrificing their beliefs is required to form a synergy between religion and customs. These conditions are found in the Muslim community of Pegayaman village, Bali. Despite the fact that they are a minority, they can integrate with local customs, which have solid Hindu characteristics. Various Balinese customs that go hand in hand with religious activities could be found easily.The synergy between religion and customs in Bali Muslim society is intriguing to research as a model for a pluralistic society and a means of introducing customs and traditions through scientific publications. The key to the well-performed synergy between religion and customs lies in the emotional sensitivity of respecting and loving each other as fellow human beings and maintaining traditions by internalizing religious values. This can be seen in the unique naming of the Muslim community. They add family names according to Balinese traditions, such as Wayan, Putu, and Gede, as first names before putting Islamic names. For this reason, this research will discuss the existence of Muslims as a minority and forms of synergy between religion and customs of the Muslim community in Pegayaman village, Buleleng sub-district, Bali.